Labour Market Power and the Dynamic Gains to Openness Reforms - Priyaranjan Jha; Antonio Rodríguez López; Adam Hal Spencer (Center for Economic Studies and ifo Institute (CESifo), 2023)
We develop a dynamic general equilibrium framework with firm heterogeneity and monopsonistic labour markets, for quantification of the impact of trade and FDI liberalisation episodes. Firms make standard extensive margin investment choices into exporting and multinational statuses. The labour market features upward-sloping supply curves and love of variety in employment. These features interact with the variable-fixed cost tradeoff of outward activity. We calibrate the model to U.S. data and study the effect of reductions in tariffs and outward FDI taxes in both bilateral and unilateral contexts, examining steady state and transitional effects. We compare the predictions of this model with a more standard version with perfectly competitive labour markets. Our headline finding is that the model with labour market power gives substantially different quantitative estimates to the perfectly competitive version. For instance, a bilateral trade liberalisation gives welfare gains that are over 10 times larger in the presence of monopsony power. Significant quantitative differences persist with a variety of robustness exercises.
Keywords: F12; F13; F16; F23; F40; H25; 330; monopsonistic labour market; trade liberalisation; love of firm variety; dynamics; foreign direct investment; corporate taxation